The Influence of Conflict and Work Stress on Employee Performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency - A. Nur Aviva Ismar; M. Hidayat; A. Muhiddin Daweng (International Journal of Economic Research and Financial Accounting, 2024)
Nur Aviva Ismar, 2024, "The Effect of Conflict and Work Stress on Employee Performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency." Thesis for the Management Study Program, Faculty of Economics and Business, Muhammadiyah University of Makassar. Supervised by Supervisor I M. Hidayat and Supervisor II H. A. Muhiddin Daweng. This research aims to partially and simultaneously examine the influence of conflict and work stress on employee performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency. Researchers distributed questionnaires to 32 employees or officials from Bajiminasa village, Rilau Ale District, Bulukumba Regency as respondents in this research. The analysis technique in this research uses data quality tests, classical assumption tests, multiple linear. regression analysis tests and hypothesis testing through the T test and F test. The results of the research show that: 1.) Partially the Conflict variable has a significant positive effect on Employee Performance at the Village Office Bajiminasa, Rilau Ale District, Bulukumba Regency. 2.) Partially, the Job Stress variable has a significant positive effect on employee performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency. 3.) Simultaneously, the Conflict and Work Stress variables have a significant positive effect on employee performance at the Bajiminasa Village Office, Rilau Ale District, Bulukumba Regency.